Functional Segregation within the Muscles of Aquatic Propulsion in the Asiatic Water Monitor (Varanus salvator) - Young, Bruce A.; Dumais, Jessica; John, Nicholas; Lyons, Brandon; Macduff, Andrew; Most, Matthew; Reiser, Nathan A.; Reiser, Peter J. (Frontiers in Physiology, 2016)
Water monitor lizards (Varanus salvator) swim using sinusoidal oscillations generated at the base of their long (50% of total body length) tail. In an effort to determine which level of the structural/organizational hierarchy of muscle is associated with functional segregation between the muscles of the tail base, an array of muscle features — myosin heavy chain profiles, enzymatic fiber types, twitch and tetanic force production, rates of fatigue, muscle compliance, and electrical activity patterns — were quantitated. The two examined axial muscles, longissimus and iliocaudalis, were generally similar at the molecular, biochemical, and physiological levels, but differed at the biomechanics level and in their activation pattern. The appendicular muscle examined, caudofemoralis, differed from the axial muscles particularly at the molecular and physiological levels, and it exhibited a unique compliance profile and pattern of electrical activation. There were some apparent contradictions between the different structural/organizational levels examined. These contradictions, coupled with a unique myosin heavy chain profile, lead to the hypothesis that there are previously un-described molecular/biochemical specializations within varanid skeletal muscles.